Plotinus and Augustine on evil and matter - Di Silva, Maurizio Filippo (Revista Archai, 2018)
The aim of this paper is to examine whether and, if so, how far, the Augustinian notion of malum is related to Plotinus’ concept of evil, as it appears in Ennead I. 8 [51]. The Augustinian notion of evil will be analyzed by focusing on the De natura boni, considering plurality and unity in Augustine’s identification of malum and nihil, both in their ontological and axiological dimensions. Topics selected for special consideration will be, first, evil as lack of modus, species and ordo naturalis (De nat. b., 4), and, secondly, corruptio as cause of defectio boni (De nat. b., 6). The second part will analyze Plotinus’ notion of evil, as spelled out in Ennead I, 8 [51], considering the Plotinian identity of to kakon and me on. Topics selected for analysis will be, first, the concept of evil as lack of measure, form and order (Enn. I. 8. 3), and secondly, the notion of to kakon as lack of good (Enn. I. 8. 5) simpliciter. The third part of this paper will consider the differences between Augustine’s and Plotinus’ identity of evil and non-being, as related to the notion of matter. Topics selected for analysis will be, firstly, Plotinus’ identity of matter and evil (Enn. I. 8. 10), and, secondly, Augustine’s concept of matter as capacitas formarum (De nat. b., 18). The conclusion will bring out how Plotinus’ concept of steresis suggests both a different relation between evil and non-being while being closely resembling Augustine’s pattern of malum and nihil.